THE INCA TREASURE: SOCIO-POLITICAL ENVIRONMENT AND HISTORICAL PROJECTION OF A BELIEF OF CONQUEST (GOVERNORATE TUCUMÁN CENTURIES XVI TO XX) - Gentile Lafaille, Margarita (2010)
One of the firmer beliefs of Conquest between the Spanish army was the story about the treasure of the Inca; the same began after the sacking of the temples of Pachacamac and Coricancha and assured that those were not the unique treasures. It was the decoy of the Hispanic explorations towards the Collasuyu. Their successive adaptations to time and place assured their survival until century XX. In this essay we tried about the incidence of this belief during Conquest and Colonization of the south of Charcas; the subject extends its consideration and study by the Folklore, and interests to the Etnohistory because it was part of the successive failures of the conservation of the Hispanic foundations and a war that lasted more than one hundred years.